The influence of different muscle mass measurements on the diagnosis of cancer cachexia. Issue 4 (26th April 2017) - Blauwhoff‐Buskermolen, Susanne; Langius, Jacqueline A.E.; Becker, Annemarie; Verheul, Henk M.W.; de van der Schueren, Marian A.E.
Abstract: Background: Progressive loss of muscle mass is a major characteristic of cancer cachexia. Consensus definitions for cachexia provide different options to measure muscle mass. This study describes the effect of different methods to determine muscle mass on the diagnosis of cancer cachexia. In addition, the association of cachexia with other features of cachexia, quality of life, and survival was explored. Methods: Prior to chemotherapy, cachexia was assessed by weight loss, body mass index, and muscle mass measurements, the latter by mid‐upper arm muscle area (MUAMA), computed tomography (CT) scans, and bio‐electrical impedance analysis (BIA). In addition, appetite, inflammation, muscle strength, fatigue, quality of life, and survival were measured, and associations with cachexia were explored. Results: Included were 241 patients with advanced cancer of the lung (36%), colon/rectum (31%), prostate (18%), or breast (15%). Mean age was 64 ± 10 years; 54% was male. Prevalence of low muscle mass was as follows: 13% with MUAMA, 59% with CT, and 93% with BIA. In turn, the prevalence of cachexia was 37, 43, and 48%, whereby weight loss >5% was the most prominent component of being defined cachectic. Irrespective of type of muscle measurement, patients with cachexia presented more often with anorexia, inflammation, low muscle strength, and fatigue and had lower quality of life. Patients with cachexia had worse overall survival compared with patients without cachexia: HRs 2.00 (1.42–2.83) with MUAMA, 1.64 (1.15–2.34) with CT, and 1.50 (1.05–2.14) with BIA. Conclusions: Although the prevalence of low muscle mass in patients with cancer depended largely on the type of muscle measurement, this had little influence on the diagnosis of cancer cachexia (as the majority of patients was already defined cachectic based on weight loss). New studies are warranted to further elucidate the additional role of muscle measurements in the diagnosis of cachexia and the association with clinical outcomes.